Development and validation of a UV spectrophotometric method for biowaiver studies in pyrazinamide tablets - Vanessa Saldaña-Bobadilla; Cintia P. Barreto-Villanueva; Frizzi J. Ganoza-Gasco; Enma Perez-Chauca; Olga E. Caballero-Aquiño; Ana E. Mantilla-Rodriguez; Pedro M. Alva-Plasencia; Maria S. Aurora-Prado (Journal of Pharmacy & Pharmacognosy Research, 2024)
Context: For regulatory reasons, a biowaiver is characterized as the substitution or exemption of bioavailability and/or bioequivalence research with in vitro dissolution tests, according to the Biopharmaceutical Classification System (BCS). These studies need validated quantification methods to give reliable results.